The Attitudes of Physiotherapy Students Toward Occupational Medicine - Prendushi, Henrrik (European Scientific Journal, ESJ, 2016)
Diseases and work-related injuries make an important part in the global burden of disease. These are studied, prevented and treated by occupational professionals as well as other health care professionals. Physiotherapists have an important role in rehabilitation of the people suffering from different workrelated injuries and diseases. Our study aims to know the attitudes of the students of Physiotherapy regarding the Occupational Medicine, in its general character, as well as their perceptions about the Albanian reality, the future of this medical science in Albania, and the relations with their profession. An anonymous questionnaire was distributed to the third year students of Physiotherapy at the University Luigj Gurakuqi in Shkodra, in their first lesson of Occupational Medicine. It consisted of 23 questions, some of them in the form of a 5 point Likert. The questionnaire was made in two parts: demographic data and the research data. The questionnaire was completed by 31 students. There is a good level of knowledge of foreign languages, 27 of them know English. The need to study the subject resulted in 3.90 points on a 5 point Likert. The degree of awareness of occupational medicine in Albania resulted in 2.03 points and the implementation of the laws in just 1.90 points, but more than 90% of the students affirm that there is an increased interest on occupational medicine during last 5 years in the country. They unanimously agree about the relationships between their profession and the occupational medicine. The majority of the students are interested about more training, and for more than one half it is a career option, too.